Seeking a Taste for Life in the Face of Our Fragility - Ramsey, Ramsey Eric (Ruch Filozoficzny, 2020)
Despite numerous cases of human endurance and survival, we remain fragile beings. We are unquestionably vulnerable and we have been so from the beginning: that is what finitude is. What is important is that the impression that such stories make on us is proof of how fragile and sensitive they are to our everyday understanding. We are constantly exposed to the risk of physical and mental suffering. Heidegger says that an understanding of our fragility is always tacitly given as yet undefined and distant. Because of its crucial importance to who and how we are, we try to forget about it. However, if we recognize its importance to our life, we can understand that there is great virtue in our vulnerability and fecundity in our fragility.